Inovasi Teknologi Plecing Kaleng Sebagai Pemulihan Ekonomi Pasca Gempa Lombok - Agung Prayogo; Chadziqatun Najilatil Mazda (Jurnal Informatika Teknologi dan Sains, 2021)
Lombok is one of the provinces in Indonesia with many tourist destinations. In August 2018, an earthquake measuring 7 on the Richter Scale rocked the tourism destination. The Lombok earthquake has become a regional threat for the public and foreign and domestic tourists. As a result of this incident, hundreds of people were injured and at least 105 people died. The Lombok earthquake not only had an impact on damage to buildings and public facilities, but also on the tourism industry sector which plays a role in increasing the country's economic growth. The economic sector is the most significantly affected. So, we need an idea of ??economic reconciliation after the Lombok earthquake. One of them is through technological innovation in the form of canning plecing kale which is one of Lombok's special foods, consisting of boiled kale and served with tomato sauce. The results showed that the technological innovation of canning plecing kale is able to make this type of food more durable and easy to consume as well as a choice of souvenirs for Lombok domestic and foreign tourists. Through technological innovation of canning plecing kale, it is hoped that the economic reconciliation of the Lombok people after the earthquake by utilizing existing local potential. Thus, in the long term, participate as a solution in the field of sustainable tourism for the Lombok area which is an object of tourist destinations.